The impact of combined exposure to triphenyltin and microplastics on the oxidative stress, energy metabolism, and digestive function of common carp (Cyprinus carpio) - Li, Ping; Wu, Yiqun; Zhang, Siqi; Li, Tengzhou; Liu, Chang; Liu, Ling; Li, Zhi-Hua (Frontiers in Environmental Science, 2025)
With the increasing presence of emerging pollutants in the environment, the combined toxic effects of organotin compounds and microplastics on aquatic organisms have garnered significant attention. This study investigated the individual and combined toxic effects of triphenyltin (TPT, 1 μg/L) and microplastics (MP, 0.5 mg/L) on oxidative stress, energy metabolism, and digestive function in Cyprinus carpio over a 42-day exposure period. The results demonstrated that TPT and MP combined exposure significantly reduced glutathione (GSH) activity, enhanced the activity of inflammatory factors (IL-1β) and upregulated the expression of antioxidant and inflammatory genes (gpx and il-1β) comparing with the control group in the liver, indicating severe oxidative stress. Combined exposure exhibited complex interactive effects, potentially involving adaptive or antagonistic mechanisms. Regarding energy metabolism, TPT and MP inhibited Na+/K+-ATPase activity, disrupting ion balance in the gills, whereas combined exposure promoted the expression of genes related to fatty acid metabolism (cpt1 and lpl). The combined exposure led to a partial restoration of ion pump activity, which implies the existence of a compensatory mechanism. TPT and MP exerted an inhibitory effect on the activity of digestive enzymes in the intestines, while they triggered a compensatory reaction by upregulating the expression of digestive enzyme genes. The combined exposure vividly unveiled the complex and intertwined interactions between the inhibitory and adaptive responses, highlighting the multifaceted nature of the biological impacts under such combined stressors. This study provides essential insights into the combined toxicity of TPT and MP, highlighting their ecological risks and underscoring the need for improved environmental monitoring and management strategies.